A PHENETIC STUDY OF THE CALAMUS FLABELLATUS COMPLEX (PALMAE) IN WEST MALESIA - NASRIANTI SYAM; TATIK CHIKMAWATI; HIMMAH RUSTIAMI (Research Center for Biology, 2016)
SYAM, N., CHIKMAWATI, T. & RUSTIAMI, H. 2016. A phenetic study of the Calamus flabellatus complex (Palmae) in West Malesia. Reinwardtia 15(1): 27 - 41. — The number of species within the Calamus flabellatus complex is still under controversy because the taxonomic status of the species is not yet clear. Morphological observations were conducted on 119 collections of Calamus in the Herbarium Bogoriense (BO) and specimen images from the Singapore Herbarium (SING) and Kew Herbarium (K). The results showed that C. flabellatus complex (all species related to C. flabellatus) in West Malesia consisted of eight species and two varieties, i.e. C. acuminatus, C. amplijugus, C. congestiflorus, C. corrugatus, C. flabellatus, C. hypertrichosus, C. javensis, and C. ruvidus. They can be distinguished using several characters, i.e. leaf sheath, knee, ocrea, leaves, inflorescence, shape of fruit, number scale of fruit and seed. Calamus flabellatus var. laevibus and C. flabellatus var. congestispinosus are two new proposed varieties. Phenetic analysis of C. flabellatus complex in West Malesia divided all species into two major clusters with similarity coefficient of 46%.